2013
DOI: 10.1371/journal.pone.0054803
|View full text |Cite|
|
Sign up to set email alerts
|

T Cell Post-Transcriptional miRNA-mRNA Interaction Networks Identify Targets Associated with Susceptibility/Resistance to Collagen-induced Arthritis

Abstract: BackgroundDue to recent studies indicating that the deregulation of microRNAs (miRNAs) in T cells contributes to increased severity of rheumatoid arthritis, we hypothesized that deregulated miRNAs may interact with key mRNA targets controlling the function or differentiation of these cells in this disease.Methodology/Principal FindingsTo test our hypothesis, we used microarrays to survey, for the first time, the expression of all known mouse miRNAs in parallel with genome-wide mRNAs in thymocytes and naïve and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…These five miRNA molecules are encoded by genes located on different chromosomes; however, they have similar seed sequences (33). It has been previously reported that miR-30b may be involved in a number of processes, including inflammatory responses, malignant tumor development and epithelial mesenchymal transition (34)(35)(36)(37), and may have posi- (34)(35)(36)(37), and may have posi-(34-37), and may have positive effects on nerve repair, the inhibition of apoptosis and blood vessel regeneration (34)(35)(36)(37). A previous study has demonstrated that miR-30b is associated with the occurrence and development of human neural tube cells and their tumors; its expression is also associated with schizophrenia (38).…”
Section: Discussionmentioning
confidence: 99%
“…These five miRNA molecules are encoded by genes located on different chromosomes; however, they have similar seed sequences (33). It has been previously reported that miR-30b may be involved in a number of processes, including inflammatory responses, malignant tumor development and epithelial mesenchymal transition (34)(35)(36)(37), and may have posi- (34)(35)(36)(37), and may have posi-(34-37), and may have positive effects on nerve repair, the inhibition of apoptosis and blood vessel regeneration (34)(35)(36)(37). A previous study has demonstrated that miR-30b is associated with the occurrence and development of human neural tube cells and their tumors; its expression is also associated with schizophrenia (38).…”
Section: Discussionmentioning
confidence: 99%
“…This approach was previously described by our group (38, 47, 48). Briefly, double-stranded complementary oligonucleotide pairs containing a portion of the Hmga2 or Prpsap1 3′ UTR with the predicted miRNA binding sites were synthetized by Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between estrogen deficiency‐induced bone loss and distinct mRNA/miRNA expression profiles has been investigated in the regulation of bone mass, mainly in apendicular bones such as tibia and femur (An et al, ). The knowledge of the functional roles of different genes and their participation in biological processes in conditions like osteoporosis may be achieved through genome research, helping to identify and compare gene expression profile in different environmental conditions (Donate et al, ). Although mRNA is not the final product of a gene, the information on transcript level is necessary to understand the regulatory gene network.…”
Section: Introductionmentioning
confidence: 99%